2010
DOI: 10.2967/jnumed.110.075507
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatocellular Carcinoma with PET/CT: A Prospective Comparison of18F-Fluorocholine and18F-FDG in Patients with Cirrhosis or Chronic Liver Disease

Abstract: This prospective study aimed to compare the diagnostic performance of 18 F-fluorocholine and 18 F-FDG for detecting and staging hepatocellular carcinoma (HCC) in patients with chronic liver disease and suspected liver nodules. Methods: Whole-body PET/CT was performed in a random order at 10 min after injection of 4 MBq of 18 F-fluorocholine per kilogram and at 1 h after injection of 5 MBq of 18 F-FDG per kilogram. PET/CT results were read in a masked manner by 2 specialists, and diagnostic performance was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
144
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(156 citation statements)
references
References 27 publications
7
144
1
4
Order By: Relevance
“…In other organs, such as the liver, the tumor can be detected despite moderate normal liver tissue uptake. A compared study of FCH-PET and FDG-PET showed that FCH was significantly more sensitive than FDG at detecting hepatocellular carcinoma, particularly in well-differentiated forms; furthermore, FCH was also effective in differentiating hepatocellular adenoma from focal nodular hyperplasia [45]. In summary, FCH is a promising PET tracer for tumor imaging when FDG-PET has a high background uptake.…”
Section: Cholinementioning
confidence: 95%
“…In other organs, such as the liver, the tumor can be detected despite moderate normal liver tissue uptake. A compared study of FCH-PET and FDG-PET showed that FCH was significantly more sensitive than FDG at detecting hepatocellular carcinoma, particularly in well-differentiated forms; furthermore, FCH was also effective in differentiating hepatocellular adenoma from focal nodular hyperplasia [45]. In summary, FCH is a promising PET tracer for tumor imaging when FDG-PET has a high background uptake.…”
Section: Cholinementioning
confidence: 95%
“…Talbot et al [45] recently proposed more evidence on the topic of FDG and F-Ch in the evaluation of primary liver cancer. Their 2010 prospective study evaluated the use of F-Ch and compared it with FDG in detecting HCC and other malignancies in patients with known cirrhosis or chronic liver disease.…”
Section: Choline Radiotracers (And Comparison With Fdg) In Hcc and Otmentioning
confidence: 99%
“…The place of other molecular imaging biomarkers is currently being evaluated, such as the18F-fluorocholine or 11C-acetate [24]. Also, some of these tumors have a high expression of somatostatine receptors and might therefore be imaged using radiolabelled octreotide and PET-CT or SPECT-CT (see lower).…”
Section: Pre-treatment Tumor Extension Assessmentmentioning
confidence: 99%
“…This neoplasm, deriving from the biliary ducts, is subdivised in 3 types: intra-hepatic, peri-hilar and extra-hepatic type. Distant metastasis can involve lymph nodes (50% at presentation), peritoneal cavity or distant organs (10-20% at presentation) [24]. Prognosis of patients with non resectable cholangiocarcinoma is generally unfavourable.…”
Section: Pre-treatment Tumor Extension Assessmentmentioning
confidence: 99%